Biological value of shrub and tree species in the Ecuadorian coast - Meza Bone, Gary Alex (2023)
The objective of this work was to evaluate six shrub and tree forage species, on their bromatological composition and in vitro digestibility during the rainy season. The treatments were T1= Morus alba harvested at 55 days; T2= Moringa oleifera harvested at 55 days; T3= Gliricidia sepium harvested at 55 days; T4= Tithonia diversifolia harvested at 55 days; T5= Erythrina poeppigiana harvested at 55 days and T6= Cratylia argentea harvested at 55 days. The variables evaluated for the bromatological composition were: dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). For in vitro digestibility of dry matter (IVDDM), in vitro digestibility neutral detergent fiber (IVDNDF) and in vitro digestibility acid detergent fiber (IVDADF). The highest (p<0.05) DM was reported by treatment T1 (27.04%), OM by treatment T5 and T1 (92.55 and 92.10%), CP by treatment T2 (19.15%), the NDF was reported by the T5 treatment (61.98%) and the ADF was reported by the T4, T6 and T5 treatments (46.15; 44.77 and 42.32%), respectively. The highest (p<0.05) IVDDM, IVDOM, IVDNDF and IVDADF was reported at T1 (72.21; 70.34; 61.64 and 41.79%) respectively. The species M. alba reported a better bromatological composition and a higher in vitro digestibility of nutrients during the rainy season.